Chrysobalanaceae endémicas del Perú - León, Blanca (2006)
The Chrysobalanaceae are represented in Peru by four genera and 98 species (Brako & Zarucchi, 1993; Ulloa Ulloa et al., 2004), all of them trees and shrubs. Here we recognize as endemics nine species and one variety in two genera. Licania is the genus with the largest number of endemic species. Endemic Chrysobalanaceae are found in the Humid Lowland Amazonian Forests region between 100 and 500 m elevation. Two endemic species have been found within Peru’s protected area system.